2017
DOI: 10.1016/j.seppur.2017.04.027
|View full text |Cite
|
Sign up to set email alerts
|

Gravity-driven membrane system for secondary wastewater effluent treatment: Filtration performance and fouling characterization

Abstract: Gravity-driven membrane (GDM) filtration is one of the promising membrane bioreactor (MBR) configurations. It operates at an ultra-low pressure by gravity, requiring a minimal energy. The objective of this study was to understand the performance of GDM filtration system and characterize the biofouling formation on a flat sheet membrane. This submerged GDM reactor was operated at constant gravitational pressure in treating of two different concentrations of secondary wastewater effluent. Morphology of biofilm l… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
20
0

Year Published

2019
2019
2023
2023

Publication Types

Select...
5
4
1

Relationship

2
8

Authors

Journals

citations
Cited by 80 publications
(23 citation statements)
references
References 32 publications
3
20
0
Order By: Relevance
“…A similar trend was observed for the biomass roughness, with the highest value for APMBRRLX (0.58), followed by the APMBRBW (0.43) and APMPBRCT (0.27). The behavior of the biomass formed with no control strategy (APMPBRCT) is in agreement with results reported in previous studies on membrane performance without applying physical cleaning showing a decrease in roughness and a tendency towards more compact and dense morphology at early stages (Pathak et al, 2018;Wang et al, 2017). A different trend was found for the APMBRBW and APMBRRLX, showing a constant and higher value in relative roughness during the whole period of observation.…”
Section: In-situ Monitoring Of Algae Formationsupporting
confidence: 90%
“…A similar trend was observed for the biomass roughness, with the highest value for APMBRRLX (0.58), followed by the APMBRBW (0.43) and APMPBRCT (0.27). The behavior of the biomass formed with no control strategy (APMPBRCT) is in agreement with results reported in previous studies on membrane performance without applying physical cleaning showing a decrease in roughness and a tendency towards more compact and dense morphology at early stages (Pathak et al, 2018;Wang et al, 2017). A different trend was found for the APMBRBW and APMBRRLX, showing a constant and higher value in relative roughness during the whole period of observation.…”
Section: In-situ Monitoring Of Algae Formationsupporting
confidence: 90%
“…Previous studies have shown that the GDM systems could potentially treat greywater/municipal wastewater, but with a relatively low permeability (30-70 L/m 2 h/bar), which is dependent on the wastewater quality such as organic concentrations (Ding et al 2016, Ding et al 2017a, Ding et al 2017b, Jabornig and Podmirseg 2015, Wang et al 2017). In addition, the GDM systems could not fully remove dissolved organic substances, such as humic substances, building blocks, and low molecular weight substances (Ding et al 2018a, Wu et al 2019.…”
Section: Introductionmentioning
confidence: 99%
“…The possibility of capturing a fouling morphology change has been exploited by several authors. Some tests were focused on evaluating the change of morphologies linked to the change of the feed [38,39]. Experiments are often performed in membrane flowcells and compared to a control.…”
Section: Monitoring the Fouling Growth Under Continuous Operationmentioning
confidence: 99%